METODE SALAFUSH SHALIH DALAM BERINTERAKSI DENGANAL-QUR`AN - Moh Abdul Kholiq Hasan (Al-A'raf : Jurnal Pemikiran Islam dan Filsafat, 2015)
Al-Qur`an belived by Muslim as the holy book used asguidance to be able to have happy life in the world until hereafter.But the reality revealed that Muslim society seen to be fartherfrom what the holy Qur‟an wanted. The data showed that most ofthe Muslims people were not able to read the Holy Qur‟an. If theywere able to read it, they were not able to understand the Qur‟an‟scontent. If they were able to understand its content, they were notable to practice it. If there were able to practicing the Qur‟aniccontent, their practicing most incompatible with the Syariahdemand. In other words, most of the Muslim society were not ableyet to interact with the Holy Qur‟an like what have done byUlama salafush shalih: who have successed to made Al-Qur`an asstarting point to promote Islamic civilization.Key words: